How does curve sprint evolve across different age-categories in soccer players? - Filter-Ruger, Alberto; Gantois, Petrus; S. Henrique, Rafael; Olivares-Jabalera, Jesús; Robles-Rodríguez, Jose; Santalla, Alfredo; Requena, Bernardo; Nakamura, Fabio Y. (Biology of Sport, 2022)
Research has shown that soccer players regularly execute curved sprints during matches. The purpose of this study was to determine the age-related effects on curve sprint (CS) performance to both sides, asymmetry, and association with linear sprint (LS). Eighty-four soccer players (aged 16.1 ± 1.6 categorized in U15, U17, and U20) were recruited, who performed CS and LS tests. One-way analysis of variance (ANOVA) and effect size (ES) were used to compare CS performance between age categories, and relationships between physical performance measures were calculated using Pearson’s correlation coefficient. The main findings of this study were that: 1) there were significant differences in the “good” side CS among age groups (p < 0.001; ES from moderate to large), but not in the “weak” side CS, 2) curve asymmetry was significantly higher in U20 than U15 (p < 0.05; ES large) and U17 players (p < 0.05; ES moderate), and 3) relationships between CS and LS times decreased with age (from significant and very large [p 0.05]). This study highlights the importance of assessing and training CS in different age categories, an action that becomes less correlated with LS as age increases, with the aim of mitigating the increase in asymmetries as a result of the specialization process, focusing interventions mainly on improving the CS “weak” side.